Cantwell, Theresa Squires. Black and white photograph of three women in a yard from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra (1948)
Left to right: Eileen Squires, friend Rose, Gerald Squires. Melrose, Mass, USA.